Some zoogeographical and ecological problems concerning the benthic invertebrates of the Black Sea - Gomoiu, Marian Traian (Cercetări Marine - Recherches Marines, 2026)
Some aspects concerning the benthic invertebrates of the Black Sea are presented in the paper. The origins of the fauna, then, the problem of the newcomers (Rapana thomasiana, Mya arenaria and Rhithropanopeus harrisi tridentatus) in the Pontic basin, and the importance of the meiobenthos are discussed.